The Prospect of New Provincial Renewable Portfolio Standard in China Based on Structural Data Analysis - Bu, Yinhe; Zhang, Xingping (Frontiers in Energy Research, 2020)
The new renewable portfolio standard policy issued by China on May, 2019 stipulates specific promotion scheme of a quota obligation mainly on power supply companies and power consumers to sell or buy an increasing proportion of their electricity from renewable energy sources. The quota is essentially switched from supply side to demand side and will be provincially distributed and assessed, consequently motivating provincial power system to accommodate more renewable energy power. This paper proposes a prospect analysis by assessing completion pressure of newly-modified quota in 30 provinces across China mainland. Results show that seventeen provinces enjoy challenging completion pressure while ten provinces make it relatively easy to complete. Structural data analysis towards provincial power supply structure and electricity balance is then put forward and reveals unfavorable factors for activating completion potential. Systematical measures are correspondingly introduced from supply side, grid side and demand side of power system, with accompanying policy implications towards core position of power grid corporation and coordinated market-based mechanism simultaneously proposed.